GENOMIC VARIATION OF FIVE INDONESIAN CACAO (Theobroma cacao L.) VARIETIES BASED ON ANALYSIS USING NEXT GENERATION SEQUENCING - I Made Tasma; Dani Satyawan; Habib Rijzaani; Ida Rosdianti; Puji Lestari; Rubiyo Rubiyo (Indonesian Agency for Agricultural Research and Development, 2016)
Indonesian cacao productivity is still low mainly due to the lack availability of superior cacao planting materials. A new breeding method is necessary to expedite cacao yield improvement programs. To date, no study has yet been done to characterize Indonesian cacao varieties at the whole genome level. The objective of this study was to characterize genomic variation of five superior Indonesian cacao varieties using next-generation sequencing. Genetic materials used were five Indonesian cacao varieties, i.e. ICCRI2, ICCRI3, ICCRI4, SUL2 and ICS13. Genome sequences were mapped to the cacao reference genome sequence of Criollo variety. Sequence alignment and genomic variation discovery were done using Bowtie2 and mpileup software of Samtools, respectively. A total of 2,326,088 single nucleotide polymorphisms (SNPs) and 362,081 insertions and deletions (Indels) were obtained from this study. In average, a DNA variant was identified in every 121 nucleotides of the genome sequence. Most of the DNA variants were located outside the genes. Only 347,907 SNPs and Indels (13.18%) were located within protein coding region (exon). Among the DNA variations within exon, 188,949 SNPs caused missense mutation and 1,535 SNPs induced nonsense mutation. Unique gene-based SNPs were also discovered from this study that can be used as fingerprints for the particular cacao variety. The DNA variants obtained were excellent DNA marker resources to support cacao breeding programs. The SNPs discovered are useful as materials for genome-wide SNP chip development to be used for gene and QTL tagging of important traits for expediting national cacao breeding program.